Effects of applying floss bands on regional blood flow - Bohlen, J.; Arsenault, M.; Deane, B.; Miller, P.; Guadagno, M.; Dobrosielski, D. A. (International Journal of Exercise Science Conference Proceedings, 2014)
Compression tack and band flossing results in re-perfusion of muscle tissue that may ultimately increase range of motion (ROM) and improve joint mechanics. Whether band flossing influences regional vascular adaptations or strength has not been evaluated. Purpose: Examine the effects of 14 days of band flossing combined with joint mobilization and resistive exercise on calf blood flow and plantar/dorsi flexion strength. Methods: Five participants (age: 20 ± 1 years; men = 1, women = 4) completed 14 days of once per day bilateral therapy that included: unloaded squats (2 sets X 10 reps), heel raises (1 set X 10 reps), active dorsi flexion (1 set X 10 reps) and passive ankle mobilization. During each session, floss bands were applied proximal and distal to the patella of the experimental leg (EXP) while the contralateral leg acted as the control (CON). Resting arterial inflow and reactive hyperemic blood flow (RHBF) were assessed with venous occlusion plethysmography. An isokinetic dynamometer was used to measure plantar/dorsi flexion strength. Baseline assessments were repeated after the 14-day intervention. Results: At baseline, there were no differences between legs in average resting arterial inflow (EXP: 2.17 ± 1.39 mlŸ100ml^-1Ÿmin^-1 vs. CON: 2.22 ± 0.70 mlŸ100ml^-1Ÿmin^-1, p=0.89) or RHBF (EXP: 17.91 ± 3.79 mlŸ100ml^-1Ÿmin^-1 vs. CON: 19.14 ± 2.89 mlŸ100ml^-1Ÿmin^-1, p=0.60). Dorsi flexion peak torque at 60 degreesŸsec^-1 was similar between legs at baseline (EXP: 9.4 ± 2.7 Nm vs. CON: 10.7 ± 3.1 Nm, p=0.11). No changes from baseline were observed in RHBF for either leg. Dorsi flexion peak torque increased 22% in the EXP (p=0.06), while no change in the CON was observed. Conclusion: While strength was modified in the EXP leg, we found no change in RHBF, suggesting no adverse or beneficial effects of band flossing on vascular function. However, the implications of more rigorous protocols of longer duration on vascular health should be comprehensively examined.